The effectiveness of M-Health associated with cardiac rehabilitation on functional capacity and cardiovascular risk factors: a systematic review and meta-analysis. (14th October 2021) - Campagnolo Goncalves Toledo, A C; Soares De Almeida, N; Pierucci, A; Straioto Salomao, A; Ribeiro Lemes, I; Flavio Milanez, V; Romero Nakagaki, W; Kretli Winkelstroter Eller, L; Milanez Morgado De Abreu, M A; Bitencourt Oliveira, C
Abstract: Introduction: Smartphone applications for health (M-Health) seem to overcome barriers to access Cardiovascular Rehabilitation Programs (CRP), because of their high degree of acceptance and also their potential to influence the frequency of physical exercise in weight loss. Objective: To analyze the effectiveness of the combination of M-Health and CRP compared to CRP alone on functional capacity, adherence to CRP, management of cardiovascular risk factors in cardiac patients. Design: Systematic Review and Meta-Analysis. Methods: The following databases were used Medline via Ovid, EMBASE, Central, PEDro and SPORTDiscus via EBSCOhost from their inception until July/2020. We included randomized controlled trials investigating the effects of M-Health in combination with CRP compared to CRP alone in adults with heart disease, and the interventions with M-Health consisted of text messages, e-mails, and applications. The primary outcome of this review was functional capacity, measured by VO2peak, or self-reported physical activity (METs.min/week). PEDro scale was used to assess the methodological quality of the studies and the GRADE approach to assess the overall quality of evidence. Pooled estimates were calculated using a random effect model to obtain mean difference (MD) or standardized mean differences (SMD) and their respectives 95% confidence intervals (CI). Results: Nineteen RCTs were eligible, the median risk of bias was 7 out of 10 points. The primary endpoint was analyzed by subgroups, time of intervention and kind of type CRP, eigthteen of these studies assessed functional capacity. CRP in combination with a m-health intervention was more effective than CRP alone in improving VO2peak, ml/min/kg, (MD: 0.84, CI: 0.30 to 1.38; I 2 =0%, high quality evidence, 12 trials, n=1889) at short-term follow-up, but at medium-term follow-up (MD: 0.84, CI: −0.26 to 1.41; I 2 =0%, high quality evidence, 8 trials, n=927, ). Similarly, CRP associated with m-health was superior to CRP alone in increasing self-reported at short-term, METs.min/week, (MD:1.31, CI: −0.24 to 2.37; I 2 = not aplicable, very low quality evidence, 1 trial, n=18), and at medium-term follow-up (MD: 0.18, CI: −0.01 to 0.36; I 2 =56%, moderate quality evidence, 4 trials, n=1107). Conclusion: High quality of evidence shows that M-Health improves cardiorespiratory fitness at short-term follow-up. In addition, supervised program showed to be more effective than non-supervised. Funding Acknowledgement: Type of funding sources: None.